2007
DOI: 10.1634/stemcells.2007-0284
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Signaling and Olig1/2 Interact to Regulate the Differentiation and Maturation of Adult Oligodendrocyte Precursor Cells

Abstract: Promotion of remyelination is an important therapeutic strategy for the treatment of the demyelinating neurological disorders. Adult oligodendrocyte precursor cells (OPCs), which normally reside quiescently in the adult central nervous system (CNS), become activated and proliferative after demyelinating lesions. However, the extent of endogenous remyelination is limited because of the failure of adult OPCs to mature into myelinating oligodendrocytes (OLs) in the demyelinated CNS. Understanding the molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 78 publications
3
114
1
Order By: Relevance
“…Thus, our results are completely consistent with earlier reports, indicating the validity of OPCs analyzed in the present study. It has been reported that several members of the BMP family, such as BMP-2 and 4, have been implicated as repressors of oligodendrocyte development in vitro by shifting oligodendrocyte precursors into the astrocyte lineage (Mabie et al 1997;Grinspan et al 2000;Cheng et al 2007). Thus, we speculated that BMPs in serum may be the key factors to induce astroglial differentiation of OPCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our results are completely consistent with earlier reports, indicating the validity of OPCs analyzed in the present study. It has been reported that several members of the BMP family, such as BMP-2 and 4, have been implicated as repressors of oligodendrocyte development in vitro by shifting oligodendrocyte precursors into the astrocyte lineage (Mabie et al 1997;Grinspan et al 2000;Cheng et al 2007). Thus, we speculated that BMPs in serum may be the key factors to induce astroglial differentiation of OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…If BMPs induce OPCs to differentiate into astrocytes, the OPCs should express BMPR. Some previous reports indicated that OPCs derived from different sources all expressed BMPR (Mabie et al 1997;Kondo and Raff 2004;Cheng et al 2007). To verify whether the OPCs cultured in our system express BMP receptors, we collected the OPCs cultured in OPC-medium and then analyzed the mRNA expression of BMP receptors (BMPRIa, Ib and II) in OPCs using RT-PCR.…”
Section: Expression Of Bmp Receptor (Bmpr) Mrnas In Opcsmentioning
confidence: 98%
See 1 more Smart Citation
“…BMP4 increases the levels of Wnt (Tbx3) and Notch target genes (Jag1, Hes1, Hes5, Hey1, and Hey2) [45] . BMP and Wnt-β-catenin also upregulate ID2 [42,46] , an inhibitory factor for oPC differentiation, thereby enhancing the crosstalk among signaling pathways that are known to inhibit myelination and repair.…”
Section: Bone Morphogenetic Proteinmentioning
confidence: 99%
“…Although glial progenitor cells (GPCs) which possess the potential to become OLs exist in the adult spinal cord and proliferate in response to SCI (McTigue et al, 2001;Zai and Wrathall, 2005), the extent of spontaneous remyelination is limited (Bunge et al, 1993;Karimi-Abdolrezaee et al, 2006). The failure of spontaneous remyelination may be due to inadequate signaling for the generation of mature OLs from proliferating GPCs (Cheng et al, 2007;Talbott et al, 2005).…”
Section: Introductionmentioning
confidence: 99%